Does the presentation of true costs at the point of purchase nudge consumers toward sustainable product options? - Robert Wilken; Julien Schmitt; Florian Dost; David Bürgin (Marketing Letters, 2024)
Do true cost campaigns (TCCs)—which display prices at the point of purchase that include social and environmental negative externalities—nudge consumers toward more expensive sustainable products? From a theoretical point of view, the answer is promising: Communicating true costs means introducing external reference prices that provide a benchmark for consumers to assess price acceptability. Showing true costs triggers a general reference to the price of sustainability, and the higher price of sustainable products becomes at least partially explained by their lower “hidden costs” (i.e., costs to compensate for all environmental and social impacts). In two empirical studies, we demonstrate that for TCCs to be effective, the hidden costs for the sustainable products must be lower than those for the conventional alternatives. Interestingly, under this condition, TCCs have an effect in markets characterized by a larger (study 1) and a smaller (study 2) green gap. In both studies, we find that increased perceived price fairness explains the effect of TCCs, as measured by the relative preference for the sustainable compared to the conventional product. In addition, we see that the price difference between the two products plays a significant role in forming this preference judgment, independent of other factors included in the model and especially independent of TCC.
Keywords: 380; True costs of products; Sustainable consumption; Dual role of price; External reference prices; Price fairness